1999
DOI: 10.1146/annurev.soc.25.1.335
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants and Consequences of Workplace Sex and Race Composition

Abstract: This chapter reviews research on the determinants and consequences of race and sex composition of organizations. Determinants include the composition of the qualified labor supply; employers' preferences, including the qualifications they require; the response of majority groups; and an establishment's attractiveness, size, and recruiting methods. The race and sex composition of an establishment affects workers' cross-group contact; stress, satisfaction, and turnover; cohesion; stereotyping; and evaluation. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
358
2
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(368 citation statements)
references
References 101 publications
4
358
2
4
Order By: Relevance
“…In addition, potential causes consistent with the role congruity theory of prejudice include the lessening numerical tokenism of women in many management positions and the increasing power of women to make personnel decisions as owners of small businesses and as decision makers in larger organizations (see Reskin et al, 1999). For example, in the savings and loan industry the traditional tendency for women to hold positions at lower but not higher managerial levels decreased between 1975 and 1987 (Cohen, Broschak, & Haveman, 1998).…”
Section: Studies Of Actual Wages and Promotionmentioning
confidence: 99%
“…In addition, potential causes consistent with the role congruity theory of prejudice include the lessening numerical tokenism of women in many management positions and the increasing power of women to make personnel decisions as owners of small businesses and as decision makers in larger organizations (see Reskin et al, 1999). For example, in the savings and loan industry the traditional tendency for women to hold positions at lower but not higher managerial levels decreased between 1975 and 1987 (Cohen, Broschak, & Haveman, 1998).…”
Section: Studies Of Actual Wages and Promotionmentioning
confidence: 99%
“…Likewise, Reskin and co-authors have called for further research on the joint e ects of race and`sex' and for`race' to be de ned beyond the Black/white dichotomy (Reskin, McBrier, and Kmec 1999). In light 16 Moreover, as we noted above, the place where people were educated is a factor that may in uence occupational outcomes (Heath and Yu 2005;Platt 2005).…”
Section: Resultsmentioning
confidence: 98%
“…However, for ethnic minority people who earned their educational credentials in the country where they work, the consequences of human capital should be similar, in principle, to the outcomes observed among women and men: the higher the education level achieved, the greater the potential for making inroads into jobs with meritocratic points of entry. In summary, if achieved status and merit bu er some of the discrimination brought about by ascribed status (Carmichael and Woods 2000;Mintz and Krymkowski 2011;Reskin, McBrier, and Kmec 1999), we should observe that segregation jointly induced by ethnicity and gender, as well as any multiplicative interaction between these two dimensions, diminishes once we control for human capital.…”
Section: Robustness Checksmentioning
confidence: 93%
See 1 more Smart Citation
“…Many studies from sociological research indicates that occupation level demographics have important implications for gender, ethnicity or age based diversity in organizations (Reskin et al, 1999). A significant part of social research on stereotype formation has specified the psychological processes by which the occupational demography in organizations can influence diversity dynamics within teams Occupational demography (majority-dominated versus balanced) serves as the situational setting that can enhance the effects of relations-oriented diversity and minimize the effects of task-oriented diversity on team performance (Joshi et al,2009) According to (Brewer, 1988), once categorization-based processes are evolved, additional information about targeted group members is filtered out and individuating processes are completely blocked .These categorization-based processes are likely to influence interactions in diverse teams especially when the environment evokes negative stereotypes against certain particular demographic groups, In a recent study, Lepine et al (2002) questioned the relationship between sex and team performance and found that all-male teams (majority dominant vs. balanced) were the worst configuration for performance on a decision-making task (even though it was a masculine-type task).…”
Section: Hypothesis 1: Relations Oriented Diversity Is Likely To Havementioning
confidence: 99%